PROFIL ARGUMENTASI ILMIAH PESERTA DIDIK BERBANTUAN PADLET DENGAN PENDEKATAN SOCIOSCIENTIFIC ISSUE GELOMBANG BUNYI - Arum Wulandari (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
This study aims to analyze the scientific argumentation profile of students with the socio-scientific issue (SSI) approach in physics learning. This qualitative descriptive research uses the SSI approach. Data collection used interviews, observation, reflection, and Padlet-assisted learning techniques. The results showed that learning physics with the Padlet-assisted SSI approach could improve scientific argumentation skills. The results of the teacher's interviews, observations, and reflections show that the challenges of Padlet learning are the depth of the material and time constraints. Further, SSI research can be developed in other subjects with the principles of developing students' character and soft skills.